The effects of delousing chemical, imidacloprid, on the copepod Acartia tonsa - Målen, Christoffer (The University of Bergen, 2024)
The Norwegian aquaculture is critically important to the country’s industry and is the world largest exporter of Atlantic salmon (Salmo salar). However, the industry’s scale has led to an increase of louse pressure on both farmed and wild populations of salmonid species, with salmon louse (Lepeophtheirus salmonis) and Scottish louse (Caligus elongatus) having the greatest impact. Therefore, there are strict regulations in place to prevent louse infestations. To adhere to these regulations the industry uses chemotherapeutants and non-medical treatments. The chemotherapeutant imidacloprid was first approved for use in Norwegian aquaculture in 2021. Imidacloprid has a moiety resembling nicotine, which acts as a neurotoxin selectively targeting the insect’s central nervous system nicotinic acetylcholine receptors. Toxicity of imidacloprid has been extensively studied for insects and aquatic species, but little data for toxicity on marine species. In this study the acute toxicity of imidacloprid on the marine crustacean Acartia tonsa, using a 96-hours constant exposure and two pulse exposures, with a 24-hours and 72-hours intermediate non-exposure periods. Additionally, the stability of imidacloprid in saltwater solution was assessed during the 96-hours exposure. Raw data was further used to calculate LC and EC and make TKTD-RED-GUTS model. Experiments showed imidacloprid to be stable during the 96-hours and Acartia tonsa experiencing both immobilization and mortality in the 96-hours exposure, with EC10 = 0.06 mg/L, EC50 = 1.2 mg/L and EC90 = 25 mg/L after 24-hours and LC10 = 0.0021 mg/L, LC50 = 0.10 mg/L and LC90 = 4.3 mg/L after 96-hours. Both TKTD-RED-GUTS were poor fits compared with obtained mortality. The result obtained indicates Acartia tonsa would experience little effects based on treated release concentration, 0.30 µg/L, from the aquaculture. However, acute exposure from untreated treatment water, 20 mg/L, of imidacloprid could potentially have a significant impact on wild Acartia tonsa and potentially ...